Effect of Diode Laser versus a Combination of Sodium Trimetaphosphate with Polyacrylic Acid on Obliteration of Dentinal Tubules: An In Vitro Study - Darwish, Mostafa Abd El-hakim; Abo-Elezz, Ahmed Fawzy; Safy, Rehab Khalil (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Irradiation with diode laser and biomimetic remineralization are important methods in the treatment of hypersensitivity and dentin remineralization. AIM: The aim of the study was evaluation of the effect of diode laser versus the effect of sodium trimetaphosphate (STMP) with polyacrylic acid (PAA) on obliteration of dentinal tubules (DT). MATERIALS AND METHODS: Sixty dentin discs with a thickness of 2 mm were prepared and conditioned with EDTA for 15 s. Then, all dentin discs were divided into three main groups (20 discs each) according to the treatment method; control, diode laser treated, and STMP with PAA group (biomimetic group). Each group was subdivided into four subgroups (five discs each) according to the storage time; 2 h (To), 1 month (T1), 2 months (T2), and 3 months (T3), respectively. All samples were prepared to be analyzed after each time interval using environmental scanning electron microscope (ESEM). Comparison of differences of DT obliteration percentage made on each group before and after the treatment were performed using computer-assisted digital image analysis. RESULTS: Control group showed the least DT obliteration percentage, the samples of laser group recorded statistically significant increase in DT obliteration percentage at To in comparison to the biomimetic group. Meanwhile, at T1, there was no statistically significant difference between both laser and biomimetic groups. However, statistically significant decrease was recorded in laser group at T2 and T3, respectively. CONCLUSION: Irradiation with diode laser and biomimetic remineralization using PAA with STMP are a promising methods to obliterate opened DT effectively.